2014
DOI: 10.1007/s11219-014-9250-6
|View full text |Cite
|
Sign up to set email alerts
|

Empirical analysis of factors affecting confirmation bias levels of software engineers

Abstract: Confirmation bias is defined as the tendency of people to seek evidence that verifies a hypothesis rather than seeking evidence to falsify it. Due to the confirmation bias, defects may be introduced in a software product during requirements analysis, design, implementation and/or testing phases. For instance, testers may exhibit confirmatory behaviour in the form of a tendency to make the code run rather than employing a strategic approach to make it fail. As a result, most of the defects that have been introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…Low confirmation bias levels were observed in participants who were experienced but inactive in development or testing . No effect of company size, educational background (undergraduate) or educational level (bachelor's, master's) were observed (Calikli and Bener 2014). However, the job title (researcher) was associated with significantly lower levels of confirmation bias when compared to the rest of the job titles, which is possibly due to researchers' acquired critical and analytical skills (Calikli and Bener 2014).…”
Section: Confirmation Bias In Software Testingmentioning
confidence: 97%
See 3 more Smart Citations
“…Low confirmation bias levels were observed in participants who were experienced but inactive in development or testing . No effect of company size, educational background (undergraduate) or educational level (bachelor's, master's) were observed (Calikli and Bener 2014). However, the job title (researcher) was associated with significantly lower levels of confirmation bias when compared to the rest of the job titles, which is possibly due to researchers' acquired critical and analytical skills (Calikli and Bener 2014).…”
Section: Confirmation Bias In Software Testingmentioning
confidence: 97%
“…Later, studied the effects of experience and activeness (in development and testing), along with the logical reasoning skills gained through education, on confirmation bias. In 2014, they extended their set of factors to include job title (developer, tester, analyst, and researcher), education, development methods and company size (small and medium enterprises [SME] vs large-scale companies) (Calikli and Bener 2014). Both studies showed no effect of either development methods or experience in development and testing on confirmation bias, but as an effect of logical reasoning skills, low bias levels were observed Bener 2010, 2014).…”
Section: Confirmation Bias In Software Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Confirmation bias is a universal trait in human cognition (Kahneman & Tversky, 1982), and is detected in many different professionals, for example, in software programmers (Calikli & Bener, 2014). Such biases are relevant in the legal setting because they will tend to lead to poor decisions at every stage in the legal system.…”
Section: Introductionmentioning
confidence: 99%